1994
DOI: 10.1021/jf00040a022
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Effects of Ergovaline Isolated from Endophyte-Infected Tall Fescue Seed on Rats

Abstract: Ergovaline (EV) was isolated from Acremonium coenophialum-infected tall fescue seed. Seed (2 kg) was extracted with 20 L of 5% lactic acid in water/methanol(4:1), filtered, and passed over an Amberlite XAD-2 column. Ergovaline was eluted with MeOH, concentrated, and chromatographed on two reversedphase C18 columns (purity > 95%, 40% overall recovery). It was administered to rats (15 pg/kg of BW, ip) a t 22 "C to determine time-related acute effects on thermoregulatory ability. Rectal temperature in EV-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
4
6
0
Order By: Relevance
“…Consistent with previous studies (Zhang et al, 1994;Spiers et al, 1995), thermoneutral hypothermia was observed when rats were fed the endophyte-infected diet in the present study at 21 1C. Core temperature was reduced by more than 0.3 1C after several days on the endophyte-infected diet, and this was similar to previous studies in our lab (Settivari et al, 2006).…”
Section: Core Body Temperature and Motor Activitysupporting
confidence: 93%
“…Consistent with previous studies (Zhang et al, 1994;Spiers et al, 1995), thermoneutral hypothermia was observed when rats were fed the endophyte-infected diet in the present study at 21 1C. Core temperature was reduced by more than 0.3 1C after several days on the endophyte-infected diet, and this was similar to previous studies in our lab (Settivari et al, 2006).…”
Section: Core Body Temperature and Motor Activitysupporting
confidence: 93%
“…This lack of response is similar to that seen in long-term studies by others (Osborn et al, 1992;Aldrich et al, 1993). In addition, Zhang et al (1994) showed that rats injected with ergovaline at TN did not exhibit an acute change in tail temperature that might suggest a reduction in blood fl ow to this region. Lack of change in T re and T skin of cattle in the present study when fed the E+ diet at TN would suggest that body temperature response, in general, is not a sensitive marker under this environmental condition.…”
Section: Thermoneutral Responsesupporting
confidence: 88%
“…air Few studies have been conducted under controlled environmental conditions to verify these shifts and determine mechanisms of action. Adult rats have been tested in environmental chambers at 7\r values known to represent cold (7-9°C), thermoneutral (22°C), and hot (31-33°C) conditions following a single intraperitoneal injection of ergovaline (15|ig/kg BW; Spiers et al, 1995;Zhang et al, 1994). Hyperthermia in the hot environment was preceded by a reduction in tail skin temperature with no shift in heat production, indicating that the cause was a reduction in cutaneous heat loss (Spiers et al, 1995).…”
Section: Thermal Response Heat Tolerance and Stressmentioning
confidence: 99%